Estudo químico, análise do óleo essencial e atividades biológicas de Inga laurina (Sw.) Willd - Furtado, Fabiana Barcelos (2014)
Inga laurina (Sw.) Willd., popularly known as Angá or Ingá Branco, belongs to Leguminosae family, Inga genus, and some species of this genus are recognized due to their pharmacological and agronomic importance. The objective of this study was to provide information about I. laurina regarding to the chemical composition of the wood and stem bark and leaves essential oils. Additionally, biological activities of the extracts and oils were evaluated. Macromolecular analysis of the wood indicated higher amount of α-cellulose and hemicelluloses in the wood compared to bark. The amount of soluble and insoluble lignin in acid and the content of ash did not show quantitative variations. The seasonal chemical composition of essential oils from Inga laurina was determined by GC/MS. In the essential oil extracted from the bark during the dry season, the presence of terpenoids (30.05%) stood out, and phytol (9.76%) was the major compound identified. For the bark oil obtained during the rainy season, in addition to terpenoids (26.63%), were identified a large amount of fatty acids (46.84%), in particular palmitic acid (25.40%). Regarding the leaves\' essential oil obtained in the dry season, esters (42.35%) were the main components. The main ester present was (Z)-hex-3-enyl benzoate (10.15%) and the major compound of this oil was (Z)-hex-3-en-1-ol (14.23%). Terpenoids (33.84%), long-chain alkanes (27.04%) and fatty acids (21.72%) were the main components of the essential oil from leaves in the rainy season. Phytol (33.21%), nonacosane (21.95%) and palmitic acid (15.20%) were the major compounds identified. The antimicrobial activity against aerobic and anaerobic oral bacteria was evaluated by the microdilution method and cytotoxic activity was carried out with Vero cells. In general, all essential oils exhibited antimicrobial activity against the aerobic and anaerobic microorganisms evaluated. The better bacteriostatic effect was observed against P. gingivalis, S. mutans, S. sanguinis, S. salivarius and S. sobrinus when evaluated oils of the rainy season, with MIC values ranging from 25 to 50 mg mL-1. In contrast, ethanol crude extracts of the bark and leaves of I. laurina showed no significant antimicrobial activity (MIC < 100 μg mL-1) against the same bacteria evaluated. Analysis of selectivity index showed a higher selectivity by bacterias evaluated than toxicity to Vero cells. From the phytochemical screening and by the results obtained in the analysis of total phenols and proanthocyanidins for the ethanol extracts of bark and leaves from I. laurina, it is possible to purpose that phenolic compounds present in the samples tested are primarily responsible for efficient DPPH radical scavenging ability observed with EC50 values similar to the BHT. Thus, the promising results with respect to biological assays of oils and extracts from I. laurina encourage to additional investigations of this species.